In-hospital outcomes of transcarotid artery revascularization and carotid endarterectomy in the Society for Vascular Surgery Vascular Quality Initiative - Schermerhorn, Marc L.; Liang, Patric; Dakour-Aridi, Hanaa; Kashyap, Vikram S.; Wang, Grace J.; Nolan, Brian W.; Cronenwett, Jack L.; Eldrup-Jorgensen, Jens; Malas, Mahmoud B. (Journal of vascular surgery, 2020)
Transcarotid artery revascularization (TCAR) with flow reversal offers a less invasive option for carotid revascularization in high-risk patients and has the lowest reported overall stroke rate for any prospective trial of carotid artery stenting. However, outcome comparisons between TCAR and carotid endarterectomy (CEA) are needed to confirm the safety of TCAR outside of highly selected patients and providers. We compared in-hospital outcomes of patients undergoing TCAR and CEA from January 2016 to March 2018 using the Society for Vascular Surgery Vascular Quality Initiative TCAR Surveillance Project registry and the Society for Vascular Surgery Vascular Quality Initiative CEA database, respectively. The primary outcome was a composite of in-hospital stroke and death. A total of 1182 patients underwent TCAR compared with 10,797 patients who underwent CEA. Patients undergoing TCAR were older (median age, 74 vs 71 years; P < .001) and more likely to be symptomatic (32% vs 27%; P < .001); they also had more medical comorbidities, including coronary artery disease (55% vs 28%; P < .001), chronic heart failure (20% vs 11%; P < .001), chronic obstructive pulmonary disease (29% vs 23%; P < .001), and chronic kidney disease (39% vs 34%; P = .001). On unadjusted analysis, TCAR had similar rates of in-hospital stroke/death (1.6% vs 1.4%; P = .33) and stroke/death/myocardial infarction (MI; 2.5% vs 1.9%; P = .16) compared with CEA. There was no difference in rates of stroke (1.4% vs 1.2%; P = .68), in-hospital death (0.3% vs 0.3%; P = .88), 30-day death (0.9% vs 0.4%; P = .06), or MI (1.1% vs 0.6%; P = .11). However, on average, TCAR procedures were 33 minutes shorter than CEA (78 ± 33 minutes vs 111 ± 43 minutes; P < .001). Patients undergoing TCAR were also less likely to incur cranial nerve injuries (0.6% vs 1.8%; P < .001) and less likely to have a postoperative length of stay >1 day (27% vs 30%; P = .046). On adjusted analysis, there was no difference in terms of stroke/death (odds ratio, 1.3; 95% confidence interval, 0.8-2.2; P = .28), stroke/death/MI (odds ratio, 1.4; 95% confidence interval, 0.9-2.1, P = .18), or the individual outcomes. Despite a substantially higher medical risk in patients undergoing TCAR, in-hospital stroke/death rates were similar between TCAR and CEA. Further comparative studies with larger samples sizes and longer follow-up will be needed to establish the role of TCAR in extracranial carotid disease management.